Effects of Dual-Purpose Cover Crop and Occasional Tillage on Dryland Crop Productivity, Profitability, and Soil Properties - Logan M. Simon; Augustine K. Obour; John D. Holman; Sandra K. Johnson; Kraig L. Roozeboom (Kansas Agricultural Experiment Station Research Reports, 2024)
Grazing or haying dual-purpose cover crops (CCs) could provide an economic benefit to offset potential lost revenue when grain crop yields are decreased after CCs in dry years. However, there is concern that removing CC biomass could limit the beneficial effects of CCs for soil health and that root-limiting soil compaction may occur with grazing on no-till (NT) fields. Occasional tillage (OT) can be used to mitigate soil compaction caused from grazing CCs. The objectives of this study were to determine dual-purpose CC management and occasional tillage (OT) effects on plant-available water (PAW), crop yields, net returns, and soil properties in an NT dryland cropping system. This study was initiated in 2015 near Brownell, KS, with CCs grown in place of fallow and either hayed, grazed, or left standing. Half of each plot was tilled with a sweep plow once every three years ahead of wheat planting while the other half remained NT. Experimental design was a split-split-plot randomized complete block with four replications with all phases of the rotation present every year. Results showed that CC biomass averaged 2,800 lb/a. Grazing removed 40% of the available forage while haying removed 70%. Profile PAW at wheat planting was greater with fallow than with CCs but unaffected by tillage. Average wheat yield was unaffected by fallow management or tillage. Net returns were in the order of grazed CCs > hayed CCs > fallow = standing CCs but were unaffected by tillage on average. Fallow management had no effect on soil bulk density, which was slightly less with OT than NT. Bulk soil and particulate organic carbon were unaffected by fallow management or tillage. However, the mean weight diameter of water-stable aggregates was greater with CCs than with fallow but unaffected by tillage. Wind-erodible fraction was unaffected by fallow management but increased with OT compared to NT. These results suggest that dual-purpose CCs can provide forage for livestock, increase soil aggregate stability, maintain average crop yields, and increase net returns in NT systems. If OT is necessary to correct root-limiting soil compaction, PAW, crop yields, net returns, and soil properties are generally unaffected compared to long-term NT.
Keywords: Dryland; cover crops; forage; tillage